Coping Style of Pigs Is Associated With Different Behavioral, Neurobiological and Immune Responses to Stressful Challenges - Kanitz, Ellen; Tuchscherer, Margret; Otten, Winfried; Tuchscherer, Armin; Zebunke, Manuela; Puppe, Birger (Frontiers in Behavioral Neuroscience, 2019)
Based on the animal’s reaction to environmental challenges, consistent but different coping styles can be identified, which in turn may have consequences for health and welfare. Therefore, profound knowledge of the complex interrelationships between individual behavioral response patterns, underlying neurobiological mechanisms and immunological effects is required. The aim of this study was to examine whether pigs with different coping styles exhibit distinct behavioral, neurobiological and immune responses to stressful situations. Therefore, pigs (n=40) were classified as proactive, reactive or intermediate animals according to a repeatedly-performed backtest, and behavioral, neuroendocrine and immune alterations were analyzed without any stress before weaning on day 28 and after a stress treatment on day 32. Our results show that the behavioral responses in an open-field/novel-object test characterized proactive pigs as more active. There were no significant differences in ACTH and cortisol concentrations between pigs with different coping characteristics. However, we found that proactive pigs displayed significantly increased plasma noradrenaline levels in response to stress, which may reflect a higher sympathetic reactivity of these animals. Furthermore, the present study revealed coping style differences in mRNA expression of mineralocorticoid, glucocorticoid, oxytocin and arginine vasopressin receptors and the immediate early gene c-fos in stress-related brain regions. While proactive pigs responded to stress with higher mRNA expression of arginine vasopressin, mineralocorticoid and glucocorticoid receptors, reactive pigs displayed higher oxytocin receptor and c-fos mRNA expression, indicating different neurobiological mechanisms of distinct coping styles in response to stressful challenges. Moreover, we also found humoral immune differences between proactive, intermediate and reactive animals. Proactive pigs had a higher total serum IgA concentration before and after stress treatment, with a significant increase in response to stress compared to reactive and intermediate pigs. In contrast, stress-induced IgM concentrations only increased in reactive and intermediate animals, suggesting that the effects of coping style on humoral immunity may differ depending on the specific function of the immunoglobulin classes. In conclusion, this multidisciplinary study expands the concept of coping style in farm animals, particularly in terms of individual stress reactivity and disease susceptibility, and thus contributes to the understanding of the biology of animal welfare.